ANALISIS UNJUK KERJA AIR CONDITIONING (AC) SPLIT 2 PAARDE KRACHT (PK) MENGGUNAKAN REFRIGERANT 22 DENGAN MUSICOOL 22 TERHADAP KONSUMSI LISTRIK - Subir; Lucianus Handri Gunanto; Bustani; Susilo, Rizky Aprylianto; Agustono (Universitas Majalengka, 2024)
The total use of electrical energy in a building or structure, one of them is the use of an air conditioning (AC) system. There are still many uses of air conditioning (AC) systems based on halocarbon refrigerants (R-22) in a building or structure. Refrigerant 22 is a type of halocarbon refrigerant that is widely used in Split ACs. The author conducted research on an LG 2 PK AC by replacing the refrigerant which was still based on Refrigerant 22 with the hydrocarbon refrigerant Musicool 22, then the data results were analyzed to determine the performance of the AC. From the results of the refrigerant retrofitting carried out on March 1, 2022, it was 1,715 Watts. After replacing the refrigerant type from refrigerant 22 to Musicool 22 refrigerant, the electric current dropped to 1,305 Watts in April 2022, 1,352 Watts in May 2022 and 1,346 Watts in June. so that the electrical power efficiency was obtained by 369 Watts and the percentage of electrical power savings was 21.51% compared to March 2022. An alternative to replace halocarbon-based refrigerants in the Split air conditioning (AC) system is hydrocarbon refrigerants, this is a solution in terms of using more environmentally friendly refrigerants and a small global warming effect.